Gastrointestinal Dysfunction in Chinese Patients with Parkinson’s Disease - Xiaoling Qin; Xue Li; Zai’e Xin; Zaili Li (Parkinson's Disease)
Purpose. To observe the occurrence and influencing factors of the symptoms related to the digestive system of people at the early and middle stages of PD and of healthy controls (HCs) using a questionnaire. Method. The questionnaire was given to 108 PD patients at early and middle stages. Twelve symptoms related to the digestive system, of which seven were listed on the Parkinson’s Disease Non-Motor Symptom Scale (PD-NMSS) and the Scale for Outcomes in Parkinson’s disease-Autonomic (SCOPA-AUT) (dysgeusia, dysphagia/choking, salivation, early satiety, constipation, loose stools, and fecal incontinence) and five symptoms used in the diagnosis and treatment of PD (loss of appetite, dry mouth, mouth pain, nausea and vomiting), were used. The questionnaire was also given to HCs. Results. There was no significant difference in age, sex, height, weight, or body mass index (BMI) between the PD group and HCs. Of the 108 people at the early and middle stages of PD, the most common symptoms related to the digestive system were 64 cases of dry mouth (59.26%), 53 cases of constipation (49.07%), and 40 cases of dysgeusia (37.04%). Multivariate binary logistics regression revealed that dysgeusia (P<0.001), dysphagia (P=0.004), early satiety (P=0.001), and constipation (P=0.007) were more likely to occur in males. BMI, disease duration, and motor symptoms had no significant correlation with the symptoms related to the digestive system (P>0.05 for all). Conclusions. Dry mouth, constipation, dysgeusia, loss of appetite, early satiety, and dysphagia are the most common (and possibly characteristic symptoms) related to the digestive system in people at the early and middle stages of PD. Being male is a risk factor for dysgeusia, dysphagia, early satiety, and constipation.